Comparison of Effectiveness of Apremilast versus Methotrexate and Apremilast in Patients with Chronic Plaque Psoriasis (Journal of Fatima Jinnah Medical University, 2025)
Background: Chronic plaque psoriasis is a prevalent, immune-mediated skin disorder characterized by erythematous plaques with silvery scales. The condition significantly impacts patients’ quality of life, necessitating effective treatment strategies.Objective: To compare the efficacy of apremilast versus methotrexate plus apremilast in patients with chronic plaque psoriasis.Methods: This prospective observational study was conducted at the Outpatient Department of Dermatology Services Hospital, Lahore. After getting approval from Ethical Review Committee, sixty patients of plaque psoriasis were observed in two groups of thirty patients each, depending on which treatment they were taking. Group A patients received apremilast, while Group B received oral methotrexate combined with apremilast. The primary outcome was the achievement of PASI 75 (75% reduction in Psoriasis Area and Severity Index) after three months of treatment. Patients were followed up after 3 months for calculation of PASI.Results: The study included 34 males (56.7%) and 26 females (43.3%), with a mean age of 42.80 ± 10.68 years. The baseline PASI score significantly reduced from 28.25 ± 5.86 to 7.09 ± 2.18 after three months. The mean percentage reduction in PASI score was 69.89 ± 11.22% in Group A and 76.76 ± 9.80% in Group B. Efficacy was observed in 42.9% of patients in Group A and 57.1% in Group B, which was statistically significant (p value =0.014).Conclusion: The combination of methotrexate and apremilast was more effective than apremilast alone in treating chronic plaque psoriasis.
Keywords: Chronic plaque psoriasis; Apremilast; Methotrexate; PASI score; Efficacy